Impacts of Implantable Collamer Lens V4c Placement on Angle Measurements Made by Optical Coherence Tomography: Two-Year Follow-up - Fernández-Vigo, José Ignacio; Macarro-Merino, Ana; Fernández-Vigo, Cristina; Fernández-Vigo, José Ángel; De-Pablo-Gómez-de-Liaño, Lucía; Fernández-Pérez, Cristina; García-Feijóo, Julián (American journal of ophthalmology, 2017)
To determine iridocorneal angle changes produced after 2 years of implantable collamer lens (ICL) V4c (STAAR Surgical AG, Nidau, Switzerland) placement by Fourier-domain optical coherence tomography (FD-OCT). Prospective interventional case series. In 54 eyes of 27 myopic subjects FD-OCT iridocorneal angle measurements were made before and 1 month, 3 months, 1 year, and 2 years after ICL implant. Trabecular-iris angle (TIA), angle opening distance 500 μm from the scleral spur (AOD500), and iridotrabecular contact length (TICL) were compared among these time points and the nasal, temporal, and inferior quadrants. Preoperative TIAs were 49.5 ± 8.7, 48.3 ± 9.6, and 49.1 ±8.6 degrees for the nasal, temporal and inferior quadrants (P < .001). Corresponding values were 29.9 ± 10.4, 28.4 ± 10.8, and 28.8 ± 9.7 degrees at 1 month and 27.3 ± 8.8, 26.8 ± 8.1, and 28.9 ± 7 degrees at 2 years of follow-up, indicating angle narrowing of 39%-45% and no further narrowing beyond 1 month in the nasal (P = .133), temporal (P = .376), and inferior (P = 1.000) quadrants. Trabecular-iris contact (TIC) was observed in 8 eyes of 8 subjects, mostly only in the temporal quadrant. Mean TICL failed to vary during follow-up (307 ± 288 μm at 3 months and 225 ± 142 μm at 2 years, P = .159). In response to ICL V4c implant, considerable angle narrowing was detected at 1 month but this narrowing remained stable at 2 years. In the 8 cases of TIC, no progression of contact was observed beyond 3 months postimplant.